Exploring the Potential for Developing Person-Centred Practices in a Child and Adolescent Mental Health Inpatient Unit: A Qualitative Research Protocol - Christie Attard; Michelle L. Elliot; Paulann Grech (International Journal of Qualitative Methods)
Due to a drastic increase in child and adolescent mental health difficulties worldwide, there is a constant need to evaluate current practices and further develop person-centred practices. The importance of person-centred practices is highlighted in research worldwide. This study will look into the potential development of person-centred practices within a child and adolecent mental health in-patient unit, the Young People’s Unit. Initially the current care practices, and person-centred moments were explored, which then lead to the development of pathways to create person-centred practices. This study followed a philosophical inquiry based on the SECI model and the concept of Ba developed by Ikujiro Nonaka. Data was collected from 15 young persons admitted to the Young People’s Unit. 15 main caregivers and the healthcare professionals which were part of the multi-discplinary team within the unit. 3 Different methods were used, the Draw, Write & Tell with the young persons, semi-structured interviews with the main caregivers, and observations by the researcher using the WCCAT-R tool and the world cafe method with the multidisciplinary team. The use of different methods ensured that the methods used were age appropriate. The externalistion and combination stage of the SECI model were done collaboratively with two young persons, two main care givers and 2 healthcare professionals who were initially participants in the data collection of the research. The involvement of different stakeholder in the data analysis resulted in the investigation of different aspects of the data which otherwise may have been missed. This study also looks into how Ba was created throughout the research process, and shows how this is congruent with the principles which are adopted in person-centred research.